Pretzel twist / Muhammad Aiman Hasmizi - Hasmizi, Muhammad Aiman (Universiti Teknologi MARA, Kedah, 2025)
Rebronding the pretzel product sold by Ahmad Suhoimie's expanding internet company, "SweetyMunch," is the main subject of this study. Since its founding in 2023, SweetyMunch hos focused on offering a wide range of pretzels to suit o variety of palates. Even with its appetising products, the brand hasn't gotten the kind of publicity and marketing it needs to reach its full potential. The most well-liked flavours in its wide product line ore motcho, chocolate, and strawberry pretzels, all of which hove devoted fan bases. But with little marketing effort and little brand awareness, SweetyMunch's potential to reach a wider audience is still unrealized. The goal of this rebronding campaign is to improve the brand's identity and hove a stronger presence in the marketplace in order to overcome these obstacles. Thus, ofter various brainstorming sessions, a new logo and togline emerged. Introducing the new name Pretzel Twist, the logo is a visual representation of the brand's identity, combining the iconic pretzel shape with playful and approachable design elements The centrepiece of the logo is a stylised pretzel. symbolising the product's signature twisted shape and evoking a sense of authenticity and tradition. The typography is rounded and soft, reflecting a friendly and cheerful tone that aligns with the brand's mission to bring joy and creativity to everyday snacking.The colour palette consists of warm tones: dark brown for the pretzel outline and border. representing the baked richness of pretzels, light brown for the text, symbolising sweetness and comfort, and creamy white, which adds balance and freshness to the design. These colours harmonise to create a welcoming and appetising aesthetic that resonates with the food theme of the brand.